Electrical Characteristics of Field-Effect Transistors based on Chemically Synthesized Graphene Nanoribbons - Zschieschang, Ute; Klauk, Hagen; Mueeller, Imke B.; Strudwick, Andrew J.; Hintermann, Tobias; Schwab, Matthias G.; Narita, Akimitsu; Feng, Xinliang; Mueellen, Klaus; Weitz, R. Thomas (Advanced Electronic Materials, 2015)
The electronic properties of chemically synthesized graphene nanoribbons (GNRs) are investigated in a field-effect transistor (FET) configuration. The FETs are fabricated by dispersing GNRs into an aqueous dispersion, depositing the GNRs onto an insulating substrate, and patterning of metal contacts by electron-beam lithography. At room temperature, the GNR FET shows a large drain current of 70 μA, very good charge injection from the contacts, saturation of the drain current at larger drain-source voltages, and an on/off current ratio of 2. The small on/off current ratio can be explained by either the unfavorable transistor geometry or by the unintentional agglomeration of two or more GNRs in the channel. Furthermore, it is demonstrated that, by quantum-chemical calculations, the bandgap of a GNR dimer can be as small as 30% of the bandgap of a GNR monomer.
CRIS-Team Scopus Importer:2023-03-20
Keywords: field-effect transistor; graphene; graphene nanoribbon; solution process